Soothe. Volume 3, Meditation. [compact disc] : Music for peaceful relaxation - Brickman, Jim (Valley Entertainment, Inc., 2017)
Jim Brickman offers up the latest installment in his Sooth series, with a continuous string of music, melodies, and moments of calm that help listeners to relax and unwind.